The Association of Kidney Function Monitoring Adherence and Estimated Glomerular Filtration Rate Changes Among Patients At-Risk for Chronic Kidney Disease - Afiatin Afiatin; Andre Indrajaya; Ria Bandiara (Acta Medica Indonesiana)
Background: Kidney Disease: Improving Global Outcome in 2012 has provided recommendations to prevent CKD progression by monitoring kidney function periodically according to the CKD stage and the clinician’s adherence to these guidelines is important. This is the first study on the relationship between adherence to monitoring renal function and changes in estimated glomerular filtration rate (eGFR) in patients at risk for CKD in Indonesia. Methods: This study was a comparative observational study with a cross-sectional approach. Research subjects were electronic medical record data from the Hasan Sadikin General Hospital information system (SIRS) data collected with the SQL Server Report Builder and “HCLAB” applications on patients at risk for CKD at the Hasan Sadikin General Hospital’s Outpatient Clinic from January 2018 to March 2020. The patients’ data were taken by the total sampling technique and then processed with the Chi-Square test. Results: From 376 subjects, the results showed that poor adherence in renal function monitoring would increase the risk of decreasing eGFR by 1.51 times compared to good monitoring adherence (PR 1.51 95% CI (1.172 - 1.935); p-value 0.007). The eGFR changes were significant (p-value 0.002) with mean 10.84 ml/min/1.73m2 (95% CI: 4.17 – 17.50). Conclusion: The study demonstrated that poor renal function monitoring adherence had an association with a decrease in eGFR in a group of patients at risk for CKD.